Clustering of Raft-Associated Proteins in the External Membrane Leaflet Modulates Internal Leaflet H-Ras Diffusion and Signaling - Eisenberg, Sharon (American Society for Microbiology, 2006)
One of the least-explored aspects of cholesterol-enriched domains (rafts) in cells is the coupling between such domains in the external and internal monolayers and its potential to modulate transbilayer signal transduction. Here, we employed fluorescence recovery after photobleaching to study the effects of antibody-mediated patching of influenza hemagglutinin (HA) proteins [raft-resident wild-type HA and glycosylphosphatidylinositol-anchored HA, or the nonraft mutant HA(2A520)] on the lateral diffusion of internal-leaflet raft and nonraft Ras isoforms (H-Ras and K-Ras, respectively). Our studies demonstrate that the clustering of outer-leaflet or transmembrane raft-associated HA proteins (but not their nonraft mutants) retards the lateral diffusion of H-Ras (but not K-Ras), suggesting stabilized interactions of H-Ras with the clusters of raft-associated HA proteins. These modulations were paralleled by specific effects on the activity of H-Ras but not of the nonraft K-Ras. Thus, clustering raft-associated HA proteins facilitated the early step whereby H-Ras is converted to an activated, GTP-loaded state but inhibited the ensuing step of downstream signaling via the Mek/Erk pathway. We propose a model for the modulation of transbilayer signaling by clustering of raft proteins, where external clustering (antibody or ligand mediated) enhances the association of internal-leaflet proteins with the stabilized clusters, promoting either enhancement or inhibition of signaling.